Numerical Solutions of the Gardner Equation via Trigonometric Quintic B-spline Collocation Method - Özlem Ersoy Hepson (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The main purpose of this paper is to get the numericalsolutions of the Gardner equation which are widely used in various disciplines.For this purpose, the time integration of the system is achieved by theclassical Crank-Nicolson method owing to its large stability region. Spacediscretization is done by using the trigonometric quintic B-spline functions.Thus the Gardner equation turns into a penta diagonoal matrix equation and theThomas algorithm is applied.